Integrating Citizenship Education In The National Curriculum: Challenges And Opportunities - Akbar Aba; Ilmiawan Ilmiawan; Musdalifah Syahrir (Jurnal Edukasi Terkini, 2026)
Purpose-This article analyzes the role of Citizenship Education in shaping intelligent, responsible, and nationally committed citizens. It examines how Civics develops civic literacy, strengthens awareness of rights and obligations, and embeds Pancasila values as the moral foundation for constructive participation in society. Research Methodology/Design/Approach- literature review was conducted by examining scholarly articles, books, curriculum documents, and official publications related to Citizenship Education and character development. This approach enabled a focused synthesis of key concepts, learning objectives, and pedagogical challenges within Civics instruction. Findings-The study finds that Citizenship Education significantly contributes to developing civic knowledge, attitudes, and behaviors aligned with democratic and national values. However, its implementation is often limited by insufficient teacher competence, lack of contextual and innovative teaching methods, and weak integration of Pancasila values into classroom practices. Strengthening teacher roles as facilitators and role models is essential to enhance the effectiveness of Civics learning. Originality/Value-This article provides a concise conceptual understanding of how Citizenship Education can be optimized to foster a generation with strong civic responsibility and national identity, offering insights for improving pedagogical practice and curriculum development.